2009
DOI: 10.4102/jsava.v80i4.210
|View full text |Cite
|
Sign up to set email alerts
|

The intravenous pharmacokinetics of diminazene in healthy dogs

Abstract: Diminazene remains one of South Africa's most commonly used antiprotozoal agents for the management of babesiosis in dogs . Although the drug has been on the market for over 40 years, its intravenous pharmacokinetics are poorly known. To better understand the pharmacokinetics of the drug Berenil®, it was reconstituted in sterile water and administered intravenously to 6 adult German shepherd dogs. All 6 dogs demonstrated the previously described secondary peak in the plasma concentration versus time profile. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…29 However, discrepancies regarding EHC do exist in the literature. Some studies clearly showed the appearance of multiple peaks, 30,31 while others reported smooth curves with a single peak. [32][33][34] But with 123 I-Hyp, we believe once re-absorbed from intestines, it is rapidly and constantly taken up by hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, discrepancies regarding EHC do exist in the literature. Some studies clearly showed the appearance of multiple peaks, 30,31 while others reported smooth curves with a single peak. [32][33][34] But with 123 I-Hyp, we believe once re-absorbed from intestines, it is rapidly and constantly taken up by hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DMZ: diminazene diaceturate, QS: quinapyramine sulfate, IC: Isometamidium chloride. MAMMAN, 1993;XAVIER et al, 2002;MILLER et al, 2005;NAIDOO et al, 2009;FLORES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nos Estados Unidos, aceturato de diminazeno tem uso proibido pelo FDA (Food and Drug Administration) (Taboada & Lobetti 2006), mas, em outros países, principalmente naqueles da África, o fármaco é ainda hoje bastante utilizado no tratamento da babesiose (Collett 2000) e da tripanossomíase (Obi et al 2013) caninas, duas dentre as causas mais comuns de morte de cães na África do Sul (Collett 2000) e Nigéria (Anene et al 2006), respectivamente. Nesses dois países, aceturato de diminazeno ainda permanece sendo o agente antiprotozoário mais comumente utilizado (Naidoo et al 2009), apesar de haver relatos de resistência por determinadas cepas de Babesia gibsoni (Hwang et al 2010) e Trypanosoma brucei brucei (Anene et al 2006). Embora a intoxicação por aceturato de diminazeno tenha sido descrita em cães desde a década de 1970, existem apenas cinco citações sobre essa toxicose na literatura internacional, a saber: 1) um resumo em anais de congresso (Boyt et al 1968), 2) um relato curto de alguns casos (Losos & Crockett 1969), 3) um trabalho científi-co experimental (Naudé et al 1970), 4) um relato de um caso (van Heerden 1981) e 5) uma descrição acerca de um caso submetido ao seminário semanal (Wednesday Slide Conference) da AFIP (Armed Forces Institute of Pathology) em 2000 (AFIP 2000).…”
Section: Introductionunclassified